Comparison of the Preaching Rhetoric of Ustadz Hanan Attaki and Habib Husein Ja'far on Instagram - Muhammad Iqbal, Muhammad Iqbal (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2025)
The importance of understanding da'wah rhetoric on social media, especially Instagram, is increasing among Generation Z and Millennials. This study compares the da'wah rhetoric of Ustadz Hanan Attaki and Habib Husein Ja'far in short Instagram Reels videos to understand its application in a digital context. Using a qualitative approach and comparative research, data was collected through observation and documentation of video content. The analysis was conducted by categorizing the videos based on rhetorical themes and identifying similarities and differences in the aspects of ethos, pathos, logos, and delivery style of the two figures. The results showed that despite the differences in style, both managed to combine the principles of ethos, pathos, and logos effectively. Ustadz Hanan uses a sharp voice pitch with a relaxed style, while Habib Husein emphasizes an organized structure with a consistent rhythm. This difference emphasizes the importance of adjusting language style, voice, and body movements to the character of the audience. In addition, both use informal language and Qur'anic verse quotations to reinforce the message. The findings are expected to provide guidance for da'i in utilizing social media effectively, as well as pave the way for further research to examine social and cultural influences on da'wah reception.